Urban Drainage Channel Redesign Based on Design Flood Analysis: A Case Study of Gunung Anyar Kidul, Surabaya - Erna Dwi Rahayu; Ameylia Fatimah; Nabilla Ayu Januarista; Nur Syiefa Hidayah; Sandy Reza Al Rasyid; Aisyah Dwi Puspasari (Lembaga Penelitian dan Pengabdian kepada Masyarakat ITATS, 2026)
Rapid urban development has significantly increased impervious surfaces, resulting in higher surface runoff and frequent urban flooding. Gunung Anyar Kidul, one of the rapidly developing residential areas in Surabaya, has experienced recurring inundation due to inadequate drainage capacity. This study aims to evaluate the hydraulic performance of the existing secondary drainage channel and propose an optimal channel redesign based on the design flood discharge. Hydrological analysis was conducted using the Gumbel distribution to estimate the five-year return period rainfall, while the Rational Method was employed to calculate the design discharge following the Indonesian Standard (SNI 2415:2016). Hydraulic capacity was evaluated using Manning's equation. The results indicate that the five-year design rainfall reached 169.288 mm/day, producing a rainfall intensity of 177.087 mm/h and a design discharge of 7.583 m³/s. The existing channel capacity was only 2.793 m³/s, indicating that the drainage system is hydraulically insufficient. A redesigned trapezoidal channel with a bottom width of 1.80 m and a flow depth of 1.50 m increased the channel capacity to 7.83 m³/s, satisfying both the design discharge and the freeboard requirement specified in SNI 03-3424-1994. The findings demonstrate that channel enlargement combined with routine maintenance can substantially improve drainage performance and reduce urban flood risk in Gunung Anyar Kidul.